Metabolic conversion of β-pinene to β-ionone in rats. (2nd December 2021) - Aloum, Lujain; Semreen, Mohammad H.; Al-Tel, Taleb H.; Al-Hroub, Hamza; Mousa, Muath; Jayaraj, Richard L.; Alefishat, Eman; Adem, Abdu; Petroianu, Georg A
Abstract: Exposure to or ingestion of turpentine can alter the scent of urine, conferring it a flowery, violet-like scent. Turpentine's effect on urine was initially noticed after its use either as medicine or as a preservative in winemaking. Regardless of the source of exposure, the phenomenon requires metabolic conversion of turpentine component(s) to ionone, the molecule mainly responsible for the scent of violets. The purpose of this study was to identify the presence of ionone in the urine of rats that received β-pinene, and thus to demonstrate that the postulated conversion occurs. We treated rats intraperitoneally with normal saline (negative control), β-ionone (positive control), low-dose β-pinene (1/3 of LD50), and high-dose β-pinene (1/2 of LD50). Urine samples were collected up to 72 h after administration of the compounds, followed by gas chromatography/mass spectrometry identification of the presence of ionone. β-Ionone was found in the urine of rats exposed to both low and high doses of β-pinene. In contrast, α-ionone appears unlikely to have been formed in rats exposed to either low or high doses of β-pinene. β-pinene was converted to β-ionone, followed by partial excretion in the urine of rats. β-Ionone is a minor metabolite of β-pinene.